2021
DOI: 10.1021/jacs.1c11208
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic CeIV/ VV Oxo Clusters with Adjustable Catalytic Reactivities

Abstract: Heterometallic Ce IV /M oxo clusters are underexplored yet and can benefit from synergistic properties from combining cerium and other metal cations to produce efficient redox catalysts. Herein, we designed and synthesized a series of new Ce 12 V 6 oxo clusters with different capping ligands: Ce 12 V 6 -SO 4 , Ce 12 V 6 -OTs (OTs: toluenesulfonic acid), and Ce 12 V 6 -NBSA (NBSA: nitrobenzenesulfonic acid). Single crystal X-ray diffraction (SCXRD) for all three structures reveals a Ce 12 V 6 cubane core formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…We observed additional features at 1498, 1390, and 980 cm −1 which confirmed the presence of Ce−O, S−O, and V �O bonds, respectively. 35,49 The bands associated with the presence of CeV clusters exhibited increased intensity in the CeV@10SBA-4 sample versus the CeV@10SBA-2, which is consistent with increased CeV loading.…”
Section: ■ Introductionsupporting
confidence: 58%
“…We observed additional features at 1498, 1390, and 980 cm −1 which confirmed the presence of Ce−O, S−O, and V �O bonds, respectively. 35,49 The bands associated with the presence of CeV clusters exhibited increased intensity in the CeV@10SBA-4 sample versus the CeV@10SBA-2, which is consistent with increased CeV loading.…”
Section: ■ Introductionsupporting
confidence: 58%
“…Extensive work has demonstrated that detoxification of nerve agents through hydrolysis of labile P–X bonds (X = F, CN, S, etc.) is a promising route, while for the degradation of mustard gas, selective oxidation to sulfoxide is an effective approach. ,, Realistically, the CWAs deployed in war are usually unknown and deadly; hence, to efficiently prevent harm to human beings caused by CWAs, multifunctional catalysts that simultaneously detoxify various types of CWAs are highly desired. However, the different detoxification pathways make constructing versatile catalysts quite challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been devoted to synthesizing polyoxometalates (POMs) and their derivatives in the last couple of decades thanks to their high structural modularity and tuneable applications in various fields, including nanoreactors, synthetic reaction catalysts, electrocatalysts, photoreduction activity, and nanoscale materials. , First, POMs can also take on multifunctional building blocks through many active oxygen atoms on the surface in the construction of target materials, and second, POMs can serve as both electron-donating groups and high proton conductors, which have high-temperature stable nanochannels for proton conduction. A reliable self-assembly method to design crystalline materials is to use POMs as inorganic segments and transition metal–organic constituents as linkages and generate a large number of POM-based organic–inorganic materials. They indicate synergistic effects and multifunctionalities because of various combinations of POMs and organic ingredients/metal-organic components. For instance, Newton et al summarized self-assemblies of organo-functionalized nanomaterials based on POM building units recently; Cheng et al summed up POM-based metal–organic frameworks (PMOFs) as high-efficiency photocatalysts owing to their synergistic effect between POMs and MOFs .…”
Section: Introductionmentioning
confidence: 99%